YiQiFuMai Lyophilized Injection ameliorates tPA-induced hemorrhagic transformation by inhibiting cytoskeletal rearrangement associated with ROCK1 and NF-κB signaling pathways. (15th November 2020) - Pan, Xue-wei; Wang, Mei-juan; Gong, Shuai-shuai; Sun, Min-hui; Wang, Yan; Zhang, Yuan-yuan; Li, Fang; Yu, Bo-yang; Kou, Jun-ping
Abstract: Ethnopharmacological relevance: Thrombolytic therapy with tissue plasminogen activator (tPA) after ischemic stroke exacerbates blood–brain barrier (BBB) breakdown and leads to hemorrhagic transformation (HT). YiQiFuMai Lyophilized Injection (YQFM) is a modern preparation derived from Sheng-mai San (a traditional Chinese medicine). YQFM attenuates the BBB dysfunction induced by cerebral ischemia–reperfusion injury. However, whether YQFM can suppress tPA-induced HT remains unknown. Aim of the study: We investigated the therapeutic effect of YQFM on tPA-induced HT and explored the underlying mechanisms in vivo and in vitro to improve the safety of tPA use against stroke. Methods: Male C57BL/6J mice were subjected to 45 min of ischemia and 24 h of reperfusion. tPA (10 mg/kg) were infused 2 h after occlusion and YQFM (0.671 g/kg) was injected 2.5 h after occlusion. The in vitro effect of YQFM (100, 200, 400 μg/mL) on tPA (60 μg/mL)-induced dysfunction of the microvascular endothelial barrier in the brain following oxygen-glucose deprivation/reoxygenation (OGD/R) was observed in bEnd.3 cells. Results: YQFM suppressed tPA-induced high hemoglobin level in the brain, mortality, neurologic severity score, BBB permeability, expression and activation of matrix metalloproteinase (MMP)-9 and MMP-2, and degradation of tight-junction proteins. Furthermore, YQFM significantly blocked tPA-induced brain microvascular endothelial permeability and phosphorylation of Rho-associated kinase (ROCK)1, myosin light chain (MLC), cofilin and p65 in vivo and in vitro. Conclusion: YQFM suppressed tPA-induced HT by inhibiting cytoskeletal rearrangement linked with ROCK-cofilin/MLC pathways and inhibiting the nuclear factor-kappa B pathway to ameliorate BBB damage caused by tPA. Graphical abstract: Image 1 Highlights: Combination of YQFM with tPA increases the safety of tPA thrombolysis in MCAO mice. YQFM decreased tPA-caused brain microvascular endothelial permeability in bEnd.3 cells. YQFM suppressed HT caused by tPA linked with ROCK-MLC/Cofilin and NF-κB pathways.